TiAl-alloy-containing structure and method for producing same
By forming a direction control area in the TiAl alloy structure, the α2 phase and β phase alternately arrange and extend in the prescribed direction, the problem of insufficient mechanical properties of the TiAl alloy structure is solved, and high strength and high temperature stability are achieved.
Patent Information
- Application Number
- CN202380074686.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-24
- Filing Date
- 2023-10-24
- Publication Date
- 2025-06-10
AI Technical Summary
The structure containing TiAl alloy needs to further improve the mechanical properties.
The structure containing TiAl alloy is formed by the laminated molding method of additive manufacturing technology AM, and the solidified portion has a direction control area, the α2 phase and the β phase are alternately arranged, and extend in a predetermined direction to improve the mechanical characteristics.
The high strength of the structure and the stability of the metallographic structure at high temperatures are achieved, and the mechanical properties are significantly improved.
Smart Images

Figure CN120129761A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a structure containing a TiAl alloy. More specifically, it relates to a structure formed by a layer stacking method of additive manufacturing technology AM (Additive Manufacturing) and containing a TiAl alloy. Background Art
[0002] The TiAl alloy has a low density, a high melting point, and exhibits excellent creep strength. Therefore, it is used as components for aerospace industry applications and components for automotive industry applications. Specifically, the TiAl alloy is applied to turbine blades of aeroengines, turbocharger wheels of automotive engines, etc. For example, Japanese Unexamined Patent Application Publication No. 2020-79577 (Patent Document 1) discloses a technique of applying a TiAl alloy to a turbocharger wheel of an automotive engine.
[0003] Prior Art Documents
[0004] Patent Documents
[0005] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2020-79577 Summary of the Invention
[0006] Problems to be Solved by the Invention
[0007] However, the mechanical properties of the structure containing the TiAl alloy need to be further improved.
[0008] An object of the present invention is to provide a structure containing a TiAl alloy capable of improving mechanical properties and a manufacturing method thereof.
[0009] Solutions to the Problems
[0010] The structure of the present invention is a structure containing a TiAl alloy and includes a solidified portion made of the TiAl alloy. The metallographic structure of the solidified portion has a cross-section including a direction control region where the α 2 phase and the β phase are alternately arranged, the α 2 phase extends along a specified direction, and the β phase extends along the extension direction of the α 2 phase.
[0011] In the structure of the present invention, the cross-section of the solidified portion includes a direction control region where the α 2 phase and the β phase extend along a specified direction. The structure of the present invention has a higher strength than the polycrystalline TiAl alloy due to the direction control region. And, since the α 2 phase and the β phase extend along a specified direction, the generation of interfaces with random crystal orientations can be suppressed, and the total interface energy is low. Therefore, even in a high-temperature region, the metallographic structure is stable. Thus, through the α 2The direction control region where the α-phase and the β-phase extend in a specified direction improves the mechanical properties of the structure.
[0012] Preferably, the cross-section of the metallographic structure of the solidified part further includes γ-phase contained in the α-phase and extending in a direction intersecting with the extension direction of the α-phase. 2 contained in the phase and 2 γ-phase extending alternately with the extension direction of the α-phase.
[0013] At this time, the mechanical properties of the structure are further improved.
[0014] In the structure, preferably, the lengths of the extension directions of the α-phase and the β-phase in the above cross-section are 500 μm or more. 2 At this time, the extension direction length of the direction control region is much longer than the grain size (about 100 μm at maximum) of the grains formed by the polycrystalline structure of the TiAl alloy. Therefore, compared with the conventional polycrystalline structure of the TiAl alloy, the mechanical properties of the structure of the present invention are more excellent.
[0015] Preferably, the structure is composed of the solidified part of the TiAl alloy, and the above cross-section is composed of the direction control region.
[0016] At this time, the entire structure is substantially composed of the direction control region. Therefore, the mechanical properties are further improved.
[0017] Preferably, the structure further includes a sintered part belonging to a sintered body of an inorganic material. Here, the sintered body refers to a solid in which inorganic powder particles are heat-treated at a temperature below the melting point and inorganic powder particles are consolidated with each other to form a plurality of necks.
[0018] At this time, the mechanical properties of the structure can be adjusted to vary depending on the part or to have anisotropy in mechanical properties.
[0019] Preferably, a gap is further formed between adjacent solidified parts of the structure.
[0020] At this time, the mechanical properties of the structure can be adjusted to vary depending on the part or to have anisotropy in mechanical properties.
[0021]
[0022] The manufacturing method of the structure of the present invention includes a design process and a forming process. The design process determines the scanning method of the beam used to form the structure to be manufactured.
[0023] The forming process scans the beam based on the beam scanning method determined by the design process, melts the inorganic powder particles that are the raw materials of the structure, and forms the structure.
[0024]
[0025] In the design process, the structure to be manufactured is divided into a plurality of solidification layers in the stacking direction, and the scanning method of the beam in each solidification layer is determined.
[0026] In the forming process, the layer forming process and the melting process are alternately repeated to stack a plurality of solidification layers to form the above-mentioned structure.
[0027] In the layer forming process, inorganic powder particles are supplied to the base to form an inorganic powder layer.
[0028] In the melting process, based on the scanning method of the beam determined in the design process, the beam is scanned to melt the inorganic powder layer to form a solidification layer.
[0029] The forming process is further performed as follows: The scanning direction of the beam when forming the j-th layer (j is a natural number) solidification layer is adjusted to be parallel or 90° staggered with the scanning direction of the beam when forming the (j - 1)-th layer solidification layer; in the scanning of the beam in each layer, the beam is scanned in such a way that the width D0 of the molten pool at a position rising by an amount equivalent to the height of the inorganic powder layer from the vertex of the molten pool having a downward convex shape in a cross section perpendicular to the scanning direction of the beam and the filling pitch (hatch distance) D1, which is the interval between adjacent scan lines in the scanning of the beam in the same layer, satisfy Equation (1).
[0030] 0 < D1 / D0 ≤ 0.20 (1)
[0031] By forming the solidification layer under the above conditions, the manufacturing method of the present invention can manufacture a structure having a solidified portion with a cross section including a direction control region.
[0032] The manufacturing method of the structure of the present invention may further include a heat treatment process.
[0033] In the heat treatment process, the structure is subjected to a heat treatment with a heat treatment temperature of 600 to 1300 °C.
[0034] At this time, in the above cross section, a γ phase is formed in the α 2 phase and extends alternately with the extension direction of the α 2 phase.
[0035] Effects of the Invention
[0036] The structure containing a TiAl alloy of the present invention can improve mechanical properties. The manufacturing method of the present invention can manufacture the above-mentioned structure. Description of the Drawings
[0037] Figure 1 It is a perspective view showing an example of the structure of the present embodiment.
[0038] Figure 2 It is a photographic image of the metallographic structure in the cross-section including the Y-axis and Z-axis of the solidified portion in the structure of the first embodiment.
[0039] Figure 3 It is Figure 2 a schematic diagram of the metallographic structure image.
[0040] Figure 4 It is a photographic image of the microstructure at each part of the direction control region in the cross-section including the Y-axis and Z-axis of the solidified portion.
[0041] Figure 5 It is a graph showing the stress-strain curves of the TiAl alloy structure composed of γ-phase as a conventional TiAl alloy structure and the structure of this embodiment.
[0042] Figure 6 It is a photographic image of the metallographic structure in the cross-section including the Y-axis and Z-axis of the solidified portion of the structure of the second embodiment.
[0043] Figure 7 It is Figure 6 a schematic diagram of the metallographic structure image.
[0044] Figure 8 It is a graph showing the stress-strain curves of the structure of the first embodiment and the structure of the second embodiment.
[0045] Figure 9 It is a photographic image and a schematic diagram for explaining the crack propagation mechanism in the structure of the first embodiment and the structure of the second embodiment.
[0046] Figure 10 It is related to Figure 2 and Figure 3 a photographic image of the metallographic structure in the cross-section including the Y-axis and Z-axis of a different solidified portion.
[0047] Figure 11 It is Figure 10 a schematic diagram of the metallographic structure image.
[0048] Figure 12 It is related to Figure 6 and Figure 7 a photographic image of the metallographic structure in the cross-section including the Y-axis and Z-axis of a different solidified portion.
[0049] Figure 13 It is Figure 12 a schematic diagram of the metallographic structure image.
[0050] Figure 14 It is a perspective view of the structure of the third embodiment.
[0051] Figure 15is different from Figure 14 A perspective view of a different structure.
[0052] Figure 16 A perspective view of the structure of the fourth embodiment.
[0053] Figure 17 A schematic diagram of a laminated modeling apparatus used in the method for manufacturing the structure of the present embodiment.
[0054] Figure 18 A flowchart of the method for manufacturing the structure of the present embodiment.
[0055] Figure 19 is Figure 18 A flowchart of the design process in
[0056] Figure 20 A schematic diagram for explaining a solidified layer formed by dividing the structure in the lamination direction.
[0057] Figure 21 is a schematic diagram showing the partitioning of the solidified layer in Figure 20 by a plurality of solidification regions DA.
[0058] Figure 22 is a diagram showing the scanning path of the beam and the crystal orientation of the primary crystal β-phase when the extension directions of the α 2 phase and the β-phase of the solidified part are set as the lamination direction Z.
[0059] Figure 23 is a diagram showing the scanning path of the beam and the crystal orientation of the primary crystal β-phase when the extension directions of the α 2 phase and the β-phase of the solidified part are set at 45° with respect to the lamination direction Z.
[0060] Figure 24A A schematic diagram for explaining the relationship between the filling pitch and the width of the molten pool.
[0061] Figure 24B is different from Figure 24A Another schematic diagram for explaining the relationship between the filling pitch and the width of the molten pool.
[0062] Figure 25 is Figure 18 A flowchart of the forming process in
[0063] Figure 26 is a diagram showing Figure 25 A schematic diagram of one process of the forming process in
[0064] Figure 27 is a diagram showing the process following Figure 26 A schematic diagram of the subsequent process.
[0065] Figure 28 is a schematic diagram showing the process subsequent to Figure 27 .
[0066] Figure 29 is a schematic diagram showing the process subsequent to Figure 28 .
[0067] Figure 30 is a schematic diagram showing the process subsequent to Figure 29 .
[0068] Figure 31 is a schematic diagram showing the process subsequent to Figure 30 .
[0069] Figure 32 is a cross-sectional photograph of a structure manufactured by a manufacturing method different from the manufacturing method of the present embodiment. Detailed Embodiments
[0070] [First Embodiment]
[0071] Figure 1 is a perspective view showing an example of the structure of the present embodiment. The structure includes one or more solidified portions SA. The solidified portion SA is made of a TiAl alloy. Specifically, the solidified portion SA is formed by solidifying the melted TiAl alloy. The structure may also be composed of one solidified portion SA.
[0072] The TiAl alloy constituting the solidified portion SA is an alloy containing Ti and Al. The chemical composition of the TiAl alloy may be a known chemical composition. The TiAl alloy may contain, for example, one or more selected from the group consisting of V, Mo, Fe, Cr, Mn, Ni, Nb, Co, Ta, and W as elements for stabilizing the β phase to replace a part of Al in the chemical composition composed of Ti and Al. The TiAl alloy constituting the solidified portion SA may further contain one or more selected from the group consisting of B, C, O, and N to replace a part of Ti or a part of Al.
[0073] The TiAl alloy contains, for example, 30 to 70% of Ti, 20 to 60% of Al, and a total of 0 to 20% of one or more selected from the group consisting of V, Mo, Fe, Cr, Mn, Ni, Nb, Co, Ta, W, B, C, O, and N in atomic %.
[0074] The TiAl alloy is composed of one or more selected from the group consisting of Ti-44Al-6Nb-1.2Cr, Ti-44Al-4Cr, Ti-(42-45)Al-(1-10)Nb-(0-0.5)B (TNM alloy), Ti-46Al-8Nb-1Cr-0.3Si-0.3Ni, Ti-45Al-5Nb-1Mo-0.3Y, Ti-44Al-6Nb-1.2Cr, Ti-43Al-6Nb-1Mo-1Cr, Ti-45Al-7Nb-0.1W-0.2B-0.2Y, Ti-33.5Al-4.8Nb-1.0Cr-0.2Si (DAT-TA1), Ti-31.8Al-7.5Nb-1.0Cr-0.5Si-0.03C (DAT-TA2), Ti-31.8Al-7.5Nb-1.0Cr-0.35Si-0.1C (DAT-TA3), Ti-45Al-5Nb-0.2B-0.2C (TNB-V4), Ti-48Al-0.8Mo-0.5V-0.2Si (IR-24), Ti-45Al-2Mn-2Nb-0.8 vol% TiB (45XD), and Ti-48Al-2Nb-2Cr.
[0075] It should be noted that in the description of the above TiAl alloy, the numerical values recorded in the element symbols refer to the content of the element in atomic%. In addition, in the description of the above alloys, the total content of all elements connected by "-" is 100% in atomic%. For example, the TiAl alloy of "Ti-44Al-6Nb-1.2Cr" means a chemical composition containing 44 at% of Al, 6 at% of Nb, 1.2 at% of Cr, and the balance is Ti. The TiAl alloy of "Ti-(42-45)Al-(1-10)Nb-(0-0.5)B" means a chemical composition containing 42-45 at% of Al, 1-10 at% of Nb, 0-0.5 at% of B, and the balance is Ti.
[0076] Figure 1 In, the structure body has a plurality of solidification parts SA. However, as described above, the structure body can also be composed of one solidification part SA. That is, the structure body can be a structure composed of solidification parts. The solidification part SA of the structure body is formed by the layer stacking method of the additive manufacturing technology AM (Additive Manufacturing) described later.
[0077] It should be noted that the solidification part refers to a solid formed by melting and solidifying inorganic powder particles as raw materials. Preferably, the density of the solidification part is 99.5% or more. It should be noted that Figure 2 the density of the structure body is 99.9%. Here, the density can be calculated by the following formula.
[0078] Density of packing = actual density of the structure / ideal density calculated from the chemical composition of the structure × 100
[0079] In the following description, it is assumed that the structure is arranged in Figure 1 the orthogonal coordinate system (X-axis, Y-axis, Z-axis) shown, and the description will continue. Here, the Z direction refers to the stacking direction in the stacking molding method described later. In the following description, the Z direction as the stacking direction will also be referred to as the stacking direction Z. The stacking direction Z can be determined from the appearance of the structure. In addition, it can also be determined from the shape of the molten pool after solidification of the cross-section of the structure. The molten pool will be described later.
[0080] The solidified part SA has a cross-section including a direction control region. Figure 2 is a photomicrograph of the metallographic structure in the cross-section including the stacking direction Z of the direction control region OA in the solidified part SA ( Figure 2 the cross-section including the Y-axis and the Z-axis in Figure 3 is Figure 2 a schematic diagram of the metallographic structure image of Figure 2 The photomicrograph of
[0081] See Figure 2 and Figure 3 , the cross-section of the solidified part SA includes a direction control region OA in which the α 2 phase PH1 and the β phase PH2 are alternately arranged. The α 2 phase has a crystal structure belonging to the D0 19 type structure of the hexagonal crystal system. The α 2 phase is Ti 3 Al, and the Ti site in the crystal structure can be replaced by any of the above elements (one or more selected from the group consisting of V, Mo, Fe, Cr, Mn, Ni, Nb, Co, Ta, W, B, C, O, and N). On the other hand, the β phase has a crystal structure of the B2 structure. The β phase is TiAl, and the Al site in the crystal structure can be replaced by any of the above elements.
[0082] In the direction control region OA of the solidified part SA, the α 2 phase PH1 extends along a specified direction. And the β phase PH2 extends along the same direction as the extension direction of the α 2 phase PH1. The direction control region OA is α 2A lamellar structure (sheet-like structure) in which the α phase PH1 and the β phase PH2 are arranged in a direction perpendicular to the extending direction. More specifically, a plurality of α 2 phases PH1 extend in the same direction as each other. Further, a plurality of β phases PH2 extend in the same direction as each other, and these β phases PH2 extend in the extending direction of the α 2 phase PH1. Figure 2 In 2 , the α 2 phase PH1 and the β phase PH2 extend in the stacking direction Z. However, the extending directions of the α
[0083] phase PH1 and the β phase PH2 are not limited to the stacking direction Z, and may extend in other specified directions other than the stacking direction Z. 2 phase. As a result, in the direction control region OA, a plurality of α 2 phases PH1 extending in a specified direction and a plurality of β phases PH2 extending in the extending direction of the α 2 phase are formed in a lamellar structure. Therefore, for the β phase PH2 in the direction control region OA in the structure, in the {001} pole figure, the {001} poles are concentrated at three positions. More specifically, for the β layer PH2 in the direction control region OA, it is one region having the same crystal orientation, or a plurality of regions each having the same crystal orientation, and among the <001> orientations (equivalent crystal orientation groups) of adjacent regions, the misorientation angle between the orientations with the smallest misorientation angle is within ±20°. Therefore, in the structure of the present embodiment, in almost the entire region, a plurality of α 2 phases PH1 extend in the same direction, and a plurality of β phases PH2 also extend in the same direction as the α 2 phase PH1.
[0084] Figure 4 is a photographic image of the microstructure at each part of the direction control region OA in the cross-section of the solidification part SA including the Y-axis and the Z-axis. Figure 4 The photographic image of
[0085] Figure 4 is obtained by the following method. A test piece of a structure of a TiAl alloy (Ti-44Al-6Nb-1.2Cr) was fabricated using the manufacturing method described later. The cross-section of the test piece including the Z direction (the cross-section including the Z direction and the Y direction) was mirror-polished. The mirror-polished cross-section was observed at 5000 times magnification with a scanning electron microscope to obtain the photographic image. 2 phase PH1 and the β phase PH2 have substantially the same extending direction at each part (A) to (F) of the direction control region OA. That is, Figure 4 in the direction solidification region OA shown, α2 Both the α-phase PH1 and the β-phase PH2 extend along the same Z direction. And in the <001> orientation of two regions having the same crystal orientation, the intersection angle between the orientations with the smallest intersection angle is within ±20°. Figure 4 α of the direction control region OA 2 The length in the extending direction (Z direction) of the α-phase PH1 and the β-phase PH2 is 600 μm. α of the directionally solidified region OA of the present embodiment 2 The length in the extending direction (Z direction) of the α-phase PH1 and the β-phase PH2 is 500 μm or more.
[0086] α of the direction control region OA 2 The extending direction length of the α-phase PH1 and the β-phase PH2 is much longer than the grain size (about 100 μm at maximum) of the grains formed by the polycrystalline structure of the TiAl alloy. It should be noted that the structure of the present embodiment may also be a structure composed of the solidified part of the TiAl alloy and the cross-section of the solidified part is composed of the direction control region OA. That is, the direction control region OA may be formed in the entire structure.
[0087] The conventional structure composed of the TiAl alloy is polycrystalline, and the maximum length of each grain is about 100 μm. That is, in the structure of the present embodiment, α 2 The length of the directionally solidified region where the α-phase PH1 and the β-phase PH2 extend in the same direction is much larger than the size of the grains of the conventional TiAl alloy. α 2 The longer the extending direction length of the direction control region OA where the α-phase PH1 and the β-phase PH2 extend in the same direction, the more excellent the mechanical properties can be obtained.
[0088] Figure 5 It is a diagram showing the stress-strain curves of the conventional TiAl alloy structure as a polycrystal containing the α 2 phase, β phase and γ phase and the structure composed of the TiAl alloy of the present embodiment. Figure 5 In it, the curve SS0 is the stress-strain curve at room temperature of the conventional structure. The curve SS1 is the stress-strain curve at room temperature of the structure of the present embodiment. The curve SS1 is obtained by applying a load in the stacking direction Z which is the extending direction of the α 2 phase PH1 and the β-phase PH2.
[0089] Specifically, a test piece of a conventional TiAl alloy as a polycrystal containing a γ phase (size: 2 mm × 2 mm × height 5 mm) and a test piece of the TiAl alloy (Ti-44Al-6Nb-1.2Cr) of the present embodiment composed of a direction control region OA (size: 2 mm × 2 mm × height 5 mm) were prepared. The test piece of the TiAl alloy of the present embodiment is composed of a solidified portion, and the entire cross-section of the solidified portion is the direction control region OA. Using an Instron type compression testing machine, a compression test was performed on each test piece at room temperature (25°C) in the atmosphere, and Figure 5 the true stress-true strain curve shown was obtained.
[0090] See Figure 5 . In the conventional structure (SS0), the maximum stress ST0 is about 800 MPa, while in the structure of the present embodiment, the maximum stress ST1 is 1347 MPa. As described above, the structure of the present embodiment can obtain excellent mechanical properties. As described above, the structure of the present embodiment includes a direction control region OA in which the α 2 phase PH1 and the β phase PH2 extend in the same direction. Therefore, when a load is applied in the extending direction of the α 2 phase PH1 and the β phase PH2, dislocations accumulate at the interface between the α 2 phase PH1 and the β phase PH2. Therefore, the mechanical properties of the structure of the present embodiment are improved.
[0091] It should be noted that in the structure of the present embodiment, a part of the solidified portion SA may include a region different from the direction control region OA. Preferably, the solidified portion SA is composed of the direction control region OA. Preferably, the entire structure is composed of one direction control region OA.
[0092] In the structure of the present embodiment, the extension direction lengths of the α 2 phase PH1 and the β phase PH2 in the direction control region OA may not be 500 μm or more. For example, in the structure, the extension direction lengths of the α 2 phase PH1 and the β phase PH2 in the direction control region OA may be 200 μm or more. In the direction control region OA, the extension direction lengths of each of the multiple α 2 phases and the multiple β phases may not be fixed.
[0093] [Second Embodiment]
[0094] In the structure of the first embodiment, the direction control region OA is a laminated structure including the α 2 phase and the β phase. However, the direction control region OA may also include the α 2 phase, the β phase, and other phases other than the α 2 phase and the β phase.
[0095] Figure 6 It is a photomicrograph of the metallographic structure of the direction control region OA of a cross-section (a cross-section including the Z-axis and the Y-axis) including the Z-axis of the solidified portion SA of the structure of the second embodiment. Figure 7 It is Figure 6 a schematic diagram of the metallographic structure. Figure 6 The photomicrograph was obtained by the following method. A test piece of a structure made of a TiAl alloy (Ti-44Al-6Nb-1.2Cr) was fabricated using the manufacturing method described later. The cross-section including the Z-direction (the cross-section including the Z-direction and the Y-direction) of the test piece was mirror-polished. The mirror-polished cross-section was observed at 5000 times magnification with a scanning electron microscope to obtain the photomicrograph.
[0096] See Figure 6 and Figure 7 In, the direction control region OA of the cross-section of the solidified portion SA includes α 2 phase PH1 and β phase PH2 extending along the lamination direction Z. The direction control region OA further includes a γ phase PH3. The γ phase PH3 has a crystal structure of an L1 0 type ordered structure. The γ phase PH3 is TiAl, and the Al site in the crystal structure can be replaced by any of the above elements.
[0097] The γ phase PH3 is formed within the α 2 phase PH1 and extends in a direction staggered with the extension direction of the α 2 phase PH1. Figure 6 and Figure 7 In, the direction control region OA is composed of the α 2 phase PH1, the β phase PH2, and the γ phase PH3. However, the direction control region OA may also contain the α 2 phase PH1, the β phase PH2, and the γ phase PH3, and further include other phases. The other phase is, for example, the ω phase.
[0098] Compared with the structure of the first embodiment, the structure of the second embodiment having the above structure exhibits more excellent mechanical properties. Figure 8 It is a graph showing the stress-strain curves of the structure of the first embodiment and the structure of the second embodiment. Figure 8 In, the curve SS2 is the stress-strain curve at room temperature of the structure of the second embodiment. The curve SS2 was obtained by applying a load in the lamination direction Z, which is the extension direction of the α 2 phase PH1 and the β phase PH2.
[0099] Specifically, a test piece (size: 2 mm × 2 mm × height 5 mm) of a structure of a TiAl alloy (Ti-44Al-6Nb-1.2Cr) of the second embodiment composed of a direction control region is manufactured and prepared by the manufacturing method described below. Using an Instron type compression testing machine, a compression test is performed on the test piece at normal temperature (25°C) in the atmosphere to obtain Figure 8 the true stress-true strain curve SS2 shown.
[0100] Refer to Figure 8 , in the structure of the first embodiment (curve SS1), the maximum stress ST1 is 1347 MPa, while in the structure of the second embodiment (curve SS2), the maximum stress ST2 is 1500 MPa. As described above, compared with the structure of the first embodiment, the structure of the second embodiment can obtain excellent mechanical properties.
[0101] Figure 9 are a photographic image and a schematic diagram for explaining the crack propagation mechanism in the structure of the first embodiment and the structure of the second embodiment. Figure 9 The photographic image of Figure 8 is obtained by the following method. The cross-section (cross-section including the Z direction and the Y direction) of the test piece that has undergone the compression test shown in
[0102] Figure 9 is mirror-polished. The mirror-polished cross-section is observed with a scanning electron microscope at 1800 times magnification to obtain the photographic image. Figure 9 The (A) of
[0103] shows the propagation of cracks in the structure of the first embodiment.
[0104] Refer to Figure 9 , α 2 In the case of the structure of the first embodiment where the γ phase PH3 is not formed in the phase PH1 (refer to Figure 9 the (A) of 2 ), when a crack CR1 is generated, the crack CR1 propagates along the interface between the α 2 phase PH1 and the β phase PH2. On the other hand, in the case of the structure of the second embodiment where the γ phase PH3 is formed in the α Figure 9 phase PH1 (refer to 2 the (B) of 2Interface propagation between the PH1 phase and the PH3 phase. Thus, in the case of the structure of the second embodiment, the propagation path of cracks can be complicated. As a result, compared with the structure of the first embodiment, the propagation of cracks can be suppressed. Therefore, the maximum stress of the structure of the second embodiment increases compared with the structure of the first embodiment.
[0105] As described above, in the structure of the second embodiment, the direction control region OA includes the α 2 phase PH1 and the β phase PH2, and further includes the γ phase PH3 formed in the α 2 phase PH1 and extending alternately with the extension direction of the α2 phase PH1. Therefore, compared with the structure of the first embodiment, the structure of the second embodiment can further improve the mechanical properties.
[0106] The structure of the second embodiment is formed by performing the heat treatment described below on the structure of the first embodiment.
[0107] It should be noted that in the first and second embodiments, the α 2 phase PH1 and the β phase PH2 in the direction control region OA extend along the stacking direction Z. However, the extension directions of the α 2 phase PH1 and the β phase PH2 are not limited to the stacking direction Z.
[0108] Figure 10 is Figure 2 and Figure 3 a photomicrograph of the metallographic structure of the direction control region OA in a cross section including the Y-axis and the Z-axis of a different solidification part SA, Figure 11 is Figure 10 a schematic diagram of the metallographic structure image.
[0109] Figure 10 The photomicrograph of Figure 2 is obtained by the same method as the photomicrograph of
[0110] Refer to Figure 10 and Figure 11 In the structure of the first embodiment, the extension directions of the α 2 phase PH1 and the β phase PH2 in the direction control region OA may also be inclined with respect to the stacking direction Z. Figure 10 In 2 the extension directions of the α 2 phase PH1 and the β phase PH2 are inclined 45° with respect to the stacking direction Z. Even in this case, if a load is applied in the extension directions of the α Figure 5 phase PH1 and the β phase PH2, a stress-strain curve equivalent to the stress-strain curve SS1 shown in
[0111] Figure 12 is a Figure 6 and Figure 7 photographic image of the metallographic structure of the direction control region OA of a cross-section (a cross-section including the Z-axis and the Y-axis) including the Z-axis of a solidification part SA different from Figure 13 is Figure 12 a schematic diagram of the metallographic structure image. Figure 12 The photographic image of Figure 2 is obtained by the same method as the photographic image of
[0112] See Figure 12 and Figure 13 In the structure of the second embodiment, in the direction control region OA, there are α 2 phase PH1, β phase PH2 and γ phase PH3, and the extending directions of the α 2 phase PH1 and the β phase PH2 can also be inclined with respect to the stacking direction Z. Figure 12 In 2 , the extending directions of the α 2 phase PH1 and the β phase PH2 are inclined 45° with respect to the stacking direction Z. Even in this case, if a load is applied in the extending directions of the α Figure 8 phase PH1 and the β phase PH2, a stress-strain curve equivalent to the stress-strain curve SS1 shown in
[0113] As described above, in the direction control region OA, the extending directions of the α 2 phase PH1 and the β phase PH2 are not particularly limited. As long as both the α 2 phase PH1 and the β phase PH2 extend in a specified direction and the solidification part SA forms a layered structure, the extending directions of the α 2 phase PH1 and the β phase PH2 are not particularly limited.
[0114] [Third Embodiment]
[0115] In the first and second embodiments, the structure includes one or more solidification parts SA. However, the structure may also include structural units (structural parts) in other forms in addition to the solidification part SA.
[0116] Figure 14 is a perspective view of the structure of the third embodiment. As Figure 14 shown, the structure of the third embodiment includes a solidification part SA and a sintered part SS. By adjusting the configurations of the solidification part SA and the sintered part SS in the structure, the mechanical properties of the structure can be adjusted to vary depending on the part or to have anisotropy in mechanical properties.
[0117] The sintered part SS is a sintered body of inorganic powder particles. Here, the sintered body means that inorganic powder particles are heat-treated at a temperature below the melting point, and the inorganic powder particles are consolidated with each other to form a plurality of necks. In the laminated modeling method, the sintered part SS is formed by adjusting the energy density of the beam (laser or electron beam) to sinter the inorganic powder particles. The sintered part SS can also be formed by heat-treating the laminated structure body. Specifically, during laminated modeling, the beam is irradiated on the area corresponding to the solidified part SA, and the irradiation of the beam is stopped on the area corresponding to the sintered part SS. Then, the structure body is heat-treated to form the sintered part SS. At this time, the inorganic powder particles in the area corresponding to the sintered part SS are sintered to form the sintered part SS.
[0118] Since the sintered part SS is an individual with necks formed, it is porous. That is, the sintered part SS has a plurality of pores. Therefore, the density of the sintered part SS is lower than that of the solidified part SA. As a result, its strength is lower than that of the solidified part SA. For example, in the structure body, the solidified part SA is arranged at the part where high strength is required, and the sintered part SS is arranged at the part where low strength is required. At this time, the structure body can have different mechanical properties according to the part. The arrangement of the sintered part SS is not particularly limited. Figure 15 is Figure 14 a perspective view of a structure body different from Figure 15 . In the structure body, there are a sintered part SS and a solidified part SA. The solidified part SA and the sintered part SS are laminated in the X direction. As described above, according to the required mechanical properties, the arrangements of the solidified part SA and the sintered part SS can be appropriately adjusted.
[0119] As described above, by making the structure body have not only the solidified part SA but also the sintered part SS, it can have mechanical properties different according to the part of the structure body.
[0120] [Fourth Embodiment]
[0121] Figure 16 is a perspective view of the structure body of the fourth embodiment. Refer to Figure 16 . In the structure body, there is a gap SP between adjacent solidified parts SA. Specifically, the structure body includes a plurality of solidified parts SA1 extending in the lamination direction Z and a solidified part SA2 extending in the Y direction and contacting the central part in the lamination direction Z of the plurality of solidified parts SA. The solidified part SA1 and the solidified part SA2 are integrally formed. Figure 16 In the structure body of
[0122] The structure body including the gap SP is not limited to Figure 16 . As long as the structure body includes a plurality of solidified parts SA and a gap SP formed between adjacent solidified parts SA, its shape is not particularly limited. As Figure 16As shown, the gap SP can be a partially open gap of the gap SP or a closed space surrounded by the solidified portion SA.
[0123] When the gap SP is formed between adjacent solidified portions SA, the mechanical properties can be adjusted based on the part of the structure. As in the third and fourth embodiments, in addition to the solidified portion SA, by arranging the sintered portion SS and / or the gap SP, the structure has shape anisotropy. Therefore, different mechanical properties can be obtained at each part.
[0124] [Other Embodiments]
[0125] The structure of this embodiment may also include other solidified portions in addition to the solidified portion SA made of TiAl alloy. For example, the structure of this embodiment may include the above-mentioned solidified portion SA made of TiAl alloy and other solidified portions made of an alloy different from TiAl alloy. Preferably, the structure of this embodiment is composed of the solidified portion SA made of TiAl alloy.
[0126] [Manufacturing Method of the Structure]
[0127] Hereinafter, the manufacturing method of the structure of this embodiment will be described. The structure of this embodiment is manufactured by the layer stacking method of the additive manufacturing technology AM. In the manufacturing method based on the layer stacking method, for example, Figure 17 the layer stacking device shown is used.
[0128] [Configuration of the Layer Stacking Device]
[0129] Referring to Figure 17 , the layer stacking device 100 is a laser layer stacking device. The layer stacking device 100 includes a control device 10, a beam generating device 14, a lens system 15, a mirror (galvanometer mirror) 16, and a chamber 20.
[0130] The beam generating device 14 is a high-energy heat source that emits a beam. The beam mentioned here is a laser beam or an electron beam. The beam generating device 14 is, for example, a fiber laser, a solid laser such as a YAG laser, a CO 2 laser, etc. The lens system 15 converges the beam emitted from the beam generating device 14 to form a beam 30. The mirror 16 performs the irradiation operation of the beam 30. That is, the irradiation position (beam scanning position) of the beam 30 is adjusted by the mirror 16.
[0131] The chamber 20 includes a bed forming chamber 201, a powder supply chamber 202, a modeling table 203, and a coater 205.
[0132] The bed forming chamber 201 is cylindrical and has an opening at the upper end. The molding table 203 is housed in the bed forming chamber 201 and is supported so as to be able to move up and down in the vertical direction. The molding table 203 is moved up and down by a motor (not shown). A base 208 is arranged on the molding table 203.
[0133] The powder supply chamber 202 is arranged beside the bed forming chamber 201. The powder supply chamber 202 is cylindrical and has a piston 204 inside that can move up and down in the vertical direction. Inorganic powder particles 40, which are the initial materials of the structure, are stacked on the piston 204. When forming the solidified part SA, the inorganic powder particles 40 can be powder made of a TiAl alloy or powder containing Ti powder and Al powder. By the piston 204 rising, the inorganic powder particles 40 are discharged from the upper opening of the powder supply chamber 202 and supplied to the bed forming chamber 201.
[0134] The coater 205 is arranged near the upper opening of the powder supply chamber 202. The coater 205 moves in a specific direction (horizontal direction) by a motor (not shown) and shuttles between the powder supply chamber 202 and the bed forming chamber 201. Figure 17 In this case, the coater 205 moves back and forth along the L direction.
[0135] By the coater 205 moving along the L direction, the inorganic powder particles 40 discharged from the powder supply chamber 202 are moved horizontally and supplied to the bed forming chamber 201. An inorganic powder layer 206 is formed by the inorganic powder particles 40 stacked on the base 208 of the molding table 203 in the bed forming chamber 201. By the coater 205 moving along the L direction, the inorganic powder particles 40 move horizontally, thereby flattening the surface of the inorganic powder layer 206.
[0136] It should be noted that a roller can also be used instead of the coater 205. When using a roller, the inorganic powder layer 206 can be formed while arbitrarily pressing the inorganic powder particles 40 with the roller.
[0137] The control device 10 includes a central processing unit (CPU), a memory, and a storage (not shown). The storage can be an HDD (hard disk drive) or an SSD (solid state drive). Well-known CAD (Computer Aided Design) application software and CAM (Computer Aided Manufacturing) application software are stored in the storage.
[0138] The control device 10 uses a well-known CAD application software to set the three-dimensional shape of the structure to be manufactured. The control device 10 further uses CAM application software to set the manufacturing conditions based on the set three-dimensional shape. In the laminated manufacturing method, the structure is manufactured by laminating a plurality of solidified layers formed by the beam 30. The processing conditions include the processing conditions when forming each solidified layer. The control device 10 controls the beam generating device 14, the lens system 15, and the mirror 16 based on the manufacturing condition data, thereby adjusting the scanning method of the beam 30 (the energy density of the beam 30, the scanning speed, the scanning mode (scanning path, scanning direction), and the beam irradiation position, etc.).
[0139] [Regarding the manufacturing process]
[0140] The manufacturing method of the structure of the present embodiment uses the laminated manufacturing method to manufacture the structure. Figure 18 is a flowchart of the manufacturing method of the structure of the present embodiment. Refer to Figure 18 , in the manufacturing method of the present embodiment, it includes a design process S1 and a forming process S2. In the design process S1, the three-dimensional shape of the structure to be manufactured is determined. In addition, when the structure includes not only the solidified portion SA but also the sintered portion SS and / or the gap SP, in the design process S1, the configuration of the sintered portion SS and the gap SP is determined. In the design process S1, further based on the determined three-dimensional shape, the structure to be manufactured is divided into a plurality of solidified layers in the lamination direction. And, the scanning method of the beam 30 for forming the structure to be manufactured is determined.
[0141] In the forming process S2, the beam 30 is irradiated based on the determined scanning method of the beam 30, the inorganic powder particles 40 are melted, and the solidified portion SA is formed to manufacture the structure. Hereinafter, the design process S1 and the forming process S2 will be described in detail.
[0142] [Regarding the design process S1]
[0143] Figure 19 is a flowchart of the design process S1. Refer to Figure 19 , first, using the control device 10, the three-dimensional shape of the structure to be manufactured is determined. The three-dimensional shape of the structure is not particularly limited. In this example, it is assumed that the structure is in a cube shape and the description will continue.
[0144] After determining the three-dimensional shape of the structure, as Figure 20 shown, the three-dimensional shape of the structure is divided into a plurality of solidified layers SLk in the lamination direction Z (S11). Specifically, here, the structure is sliced and divided by the preset number kmax (pieces) of the solidified layers SLk (k is a natural number, and the maximum number is kmax). Sometimes the shapes of the respective solidified layers SLk of the structure are different. Therefore, the processing condition data is manufactured according to each solidified layer SLk.
[0145] It should be noted that, referring to Figure 21 , from the stacking direction Z, each solidified layer SLk can also be divided into a plurality of solidification regions DA (S12). That is, S12 is an optional process. When implementing S12, Figure 21 in , the solidification region DA is rectangular. However, the shape of the solidification region DA can also be a shape other than rectangular. The solidification region DA can be, for example, triangular or polygonal other than rectangular.
[0146] Next, the control device 10 sets the extension directions of the α 2 phase PH1 and the β phase PH2 of the solidified part SA made of TiAl alloy. For example, the extension directions of the α 2 phase PH1 and the β phase PH2 are set as the stacking direction Z (S13). Then, according to the determined orientation of the crystal orientation, the scanning method (scanning path) of the beam 30 is determined (S14).
[0147] For example, when the extension directions of the α 2 phase PH1 and the β phase PH2 of the solidified part SA are set as the stacking direction Z (that is, set as Figure 2 , Figure 3 , Figure 6 and Figure 7 the metallographic structure shown), as Figure 22 shown, when forming the j-th layer (j is a natural number) of the solidified layer SLj, the scanning direction of the beam 30 is adjusted to be parallel to the scanning direction of the beam 30 when forming the (j - 1)-th layer solidified layer SLj-1 which is the lower layer of the j-th layer. At this time, within the same layer, the scanning directions of adjacent scanning lines are not particularly limited. The scanning directions of the beam 30 of adjacent scanning lines can be the same direction as each other, as Figure 22 shown, or can be opposite directions to each other. That is, within the same layer, the beam 30 can be scanned unidirectionally (scanning in only one direction), or can be scanned back and forth. As a result, the crystal structure of the primary β phase on the orthogonal coordinate system is as Figure 22 shown. That is, the <011> orientation of the primary β phase is along the Z direction.
[0148] On the other hand, when the extension directions of the α 2 phase PH1 and the β phase PH2 of the solidified part SA are set as the direction inclined 45° with respect to the stacking direction Z (that is, set as Figures 10 to 13 the metallographic structure), as Figure 23As shown, the scanning direction of the beam 30 when forming the solidified layer SLj of the j-th layer (j is a natural number) is adjusted to be staggered by 90° (i.e., orthogonal) with respect to the scanning direction of the beam 30 when forming the solidified layer SLj-1 of the (j - 1)-th layer, which is the lower layer of the j-th layer. The scanning directions of adjacent scan lines within the same layer (or within the solidification region DA) are not particularly limited. The beam 30 can be unidirectionally scanned or reciprocally scanned. As a result, the crystal structure of the primary crystal β-phase on the orthogonal coordinate system is as Figure 23 shown. That is, the <001> orientation of the primary crystal β-phase is along the Z direction.
[0149] Through the above method, the scanning method of the beam 30 is determined (S14). It should be noted that in the process of determining the scanning method of the beam 30, the conditions of the beam 30 (the output E of the beam 30, the scanning speed, etc.) are also determined according to the energy density (J / mm 2 ) required to melt and solidify the solidified layer of the j-th layer.
[0150] Moreover, when forming the solidification part SA of the present embodiment, the filling pitch D1, which is the interval between adjacent beam scan lines in the beam scanning path, is made significantly smaller than the width D0 of the molten pool defined below. Figure 24A and Figure 24B are schematic diagrams for explaining the relationship between the filling pitch D1 of the solidification part SA for forming the structure of the present embodiment and the width D0 of the molten pool (weld bead).
[0151] Refer to Figure 24A . In a cross-section perpendicular to the scanning direction of the beam 30, the molten pool MP has a downwardly convex curved shape. Here, the vertex (the deepest position) of the downwardly convex shape of the molten pool MP is set as vertex P. In addition, the height (the layer stacking pitch described later) of the inorganic powder layer 206 formed in the forming process of the layer stacking molding method is set as Δh. At this time, the width of the molten pool MP at a position rising by an amount equivalent to Δh along the layer stacking direction Z from vertex P is defined as D0 (mm).
[0152] At this time, in the present embodiment, the filling pitch D1 and the width D0 of the molten pool MP satisfy formula (1).
[0153] 0 < D1 / D0 ≤ 0.20 (1)
[0154] Figure 24A In, the filling pitch D1 is too large with respect to the width D0 of the molten pool MP. On the other hand, Figure 24B In, the filling pitch D1 and the width D0 of the molten pool MP satisfy formula (1).
[0155] As Figure 24BAs shown, the filling pitch D1 is adjusted to be narrow enough relative to the width D0 to satisfy Equation (1). At this time, the heat flow direction of the molten pool MP in the manufacturing process can be restricted to a fixed direction, and the structure of the present embodiment can be manufactured.
[0156] The preferred upper limit of D1 / D0 is 0.18, more preferably 0.15, and even more preferably 0.12.
[0157] Specifically, as Figure 24A when the filling pitch D1 and the width D0 of the molten pool MP do not satisfy Equation (1), the heat F of the molten pool MP radially flows to the outside of the molten pool MP along the interface of the molten pool MP. On the other hand, as Figure 24B when the filling pitch D1 and the width D0 of the molten pool MP satisfy Equation (1), the direction of the heat F released from the molten pool MP will be somewhat consistent. By controlling the direction of this heat F, a single crystal or a single crystal-like β phase is first generated in the solidification part SA. Then, a part of the single crystal or single crystal-like β phase is transformed into the α 2 phase. Thereby, a structure including a direction control region OA in which the α 2 phase and the β phase extend in the same direction is manufactured.
[0158] It should be noted that Figure 24B in, although the heat F flows in a direction intersecting with the Z direction and the Y direction, the flow direction of the heat F may also flow substantially parallel to the Z direction. In short, in the case of the present embodiment Figure 24B , the heat F is fixed in any direction to some extent.
[0159] The width D0 of the molten pool MP can be confirmed by manufacturing a sample before manufacturing the structure to be manufactured and observing a cross-section including the Z direction in the sample. When the cross-section of the sample is as Figure 24A such, the width D0 of the molten pool MP can be obtained based on the shape of the molten pool MP. On the other hand, when the cross-section of the sample is as Figure 24B such that the width D0 cannot be obtained from the shape of the molten pool MP, D0 / 2 is obtained from the position of the vertex P of the molten pool MP and the recognizable shape part of the molten pool MP. The obtained D0 / 2 is multiplied by 2 times to be used as the width D0 of the molten pool MP. As described above, by manufacturing a sample before manufacturing the structure to be manufactured, the width D0 of the molten pool MP can be measured. Thereby, the scanning method of the beam 30 is adjusted.
[0160] Information about the scanning method of the beam 30 is, for example, pre-stored in a memory or a memory in the control device 10. Through the above process, the scanning method of the beam for each solidification layer SLk is determined.
[0161] [Regarding the forming process S2]
[0162] In the forming process S2, based on the scanning method of the beam 30 determined in the design process S1, beam scanning is performed to form each solidified layer SLk, thereby manufacturing the structure. It should be noted that the forming process S2 is carried out after evacuating the chamber 20.
[0163] Figure 25 is a flowchart of the forming process S2. Refer to Figure 25 , the control device 10 first sets the count k to "1" and starts forming the first solidified layer SL1 as the lowermost layer.
[0164] An inert gas (argon, nitrogen, helium, etc.) is supplied into the chamber 20 to preheat the base 208 disposed on the modeling table 203. It should be noted that during preheating, the base 208 can be preheated without supplying an inert gas after evacuation. Additionally, the base 208 can be preheated after supplying an inert gas without forming a vacuum. The preheating of the base 208 can also be omitted.
[0165] Next, the control device 10 forms the inorganic powder layer 206 (S22). The control device 10 gives an instruction to raise the piston 204 of the powder supply chamber 202, thereby discharging the inorganic powder particles 40 as the initial material of the structure. The powder supply chamber 202 discharges the inorganic powder particles 40 according to the instruction from the control device 10. At this time, as Figure 26 shown, the coater 205 moves along the L direction. Thereby, the discharged inorganic powder particles 40 move along the L direction and are supplied to the bed forming chamber 201. The inorganic powder particles 40 accumulate on the base 208 and the modeling table 203 to form the inorganic powder layer 206.
[0166] The coater 205 further moves horizontally (in the L direction) on the surface of the inorganic powder layer 206 on the base 208. At this time, the inorganic powder particles 40 move horizontally. The thickness of the lowermost inorganic powder layer 206 is, for example, about 5 to 1000 μm.
[0167] Next, the control device 10 preheats the inorganic powder layer 206 (S23). The preheating is an optional process. When preheating is performed, it can be carried out by various methods. For example, the inorganic powder layer 206 can be preheated by irradiating the beam 30, or the inorganic powder layer 206 can be preheated by raising the temperature of the modeling table 203. The inorganic powder layer 206 can also be preheated by heating the inorganic powder particles 40 in the bed forming chamber 201 with a heater.
[0168] Next, based on the beam scanning method determined by the design process S1, the inorganic powder layer 206 is scanned with the beam 30 to melt the inorganic powder layer 206, forming the first solidified layer SL1 (S24). The control device 10 reads the data of the scanning method of the beam 30 produced by the design process S1 from the memory. Based on the read scanning method of the beam 30, the control device 10 controls the beam 30.
[0169] Specifically, the control device 10 uses the determined scanning path of the beam 30 to scan the solidified layer SL1 with the beam 30. Thereby, the solidified layer SL1 is formed.
[0170] In the melting process (S24), not only the inorganic powder layer 206 but also the surface layer portion of the base 208 can be melted. The beam 30 is scanned under the above beam conditions to melt the inorganic powder layer 206, as Figure 27 shown, forming the solidified layer SL1. At this time, among the inorganic powder layer 206, the inorganic powder particles 40 disposed in the regions other than the solidified layer SL1 are neither melted nor sintered.
[0171] After forming the first solidified layer SL1, the control device 10 determines whether the count k is kmax (S25). Here, since the count k = 1 (No in S25), the control device 10 sets the count k to k + 1 = 2 (S26). Then, the control device 10 prepares for the production of the second solidified layer SL2.
[0172] The control device 10 causes the modeling table 203 to descend only by the layer stacking pitch Δh (S27). As a result, as Figure 28 shown, the surface of the inorganic powder layer 206 is lowered only by Δh compared to Figure 27 before.
[0173] After step S27 is completed, the process returns to step S22. At this time, the control device 10 forms a new inorganic powder layer 206 on the inorganic powder layer 206 on which the solidified layer SL1 is formed (S22). Specifically, according to the instruction of the control device 10, the piston 204 in the powder supply chamber 202 rises, and the inorganic powder particles 40 are discharged again. At this time, as Figure 29 shown, the coater 205 moves in the L direction. Therefore, the inorganic powder particles 40 move in the L direction, forming a new inorganic powder layer 206 having a thickness of Δh. The surface of the new inorganic powder layer 206 is flattened by the coater 205.
[0174] Next, the control device 10 preheats the inorganic powder layer 206 (S23) and forms the second solidified layer SL2 (S24). At this time, the control device 10 irradiates the inorganic powder layer 206 with the beam 30 based on the processing condition data of the k-th layer (here k = 2). As a result, as Figure 30As shown, the inorganic powder layer 206 within the area irradiated by the beam 30 melts and solidifies to form a solidified layer SL2. Through the above process, the solidified layer SL2 is stacked on the solidified layer SL1.
[0175] Next, it proceeds to step S25, and the control device 10 repeats the operations from step S22 to step S27 until k = kmax, that is, until the uppermost solidified layer SLkmax is formed. That is, the control device 10 repeats the layer formation process (S22) and the melting process (S24) until a structure with a desired three-dimensional shape is completed as Figure 31 shown.
[0176] In the present embodiment, further in the formation process (S2), the scanning direction of the beam when forming the j-th layer (j is a natural number) solidified layer SLj is adjusted to be parallel (X scanning) or at a 90° stagger (XY scanning) with the scanning direction of the beam 30 when forming the (j - 1)-th layer solidified layer SLj-1. Then, in the beam scanning within the same layer, the beam scanning is performed such that the scanning directions of adjacent scan lines are in opposite directions or the same direction as each other. Furthermore, in the beam scanning in each layer, the width D0 of the molten pool MP at a position where it rises by Δh from the vertex P of the molten pool MP having a downwardly convex shape in a cross-section perpendicular to the beam scanning direction and the filling pitch D1 which is the interval between adjacent scan lines in the beam scanning within the same layer satisfy equation (1). Through the above adjustments, the structure of the present embodiment can be realized.
[0177] By implementing the above adjustments, when the inorganic powder layer 206 melts and solidifies, first the primary crystal β-phase is generated. The generated primary crystal β-phase is a single crystal or a near single crystal. Then, as it is cooled, a part of the primary crystal β-phase PH2 transforms into the α 2 phase PH1. At this time, according to the Burgers orientation relationship, the {110} of the β-phase PH2 is parallel to the (0001) plane of the α 2 phase PH1 and the <111> orientation of the β-phase PH2 is parallel to the <11-20> orientation of the α 2 phase PH1 to generate the α 2 phase PH1.
[0178] When a part of the primary crystal β-phase PH2 transforms into the α 2 phase PH1, there are 12 variant relationships between the α2-phase PH1 and the β-phase PH2 where the {110} of the β-phase PH2 is parallel to the (0001) plane of the α 2 phase PH1 and the <111> orientation of the β-phase PH2 is parallel to the <11-20> orientation of the α 2 phase PH1.
[0179] In the present embodiment, as Figure 24BAs shown, the beam 30 is scanned in such a way that the width D0 of the molten pool MP and the filling pitch D1 satisfy the formula (1). Thus, as Figure 24B shown, the flow direction of the heat F is fixed. As a result, among the 12 azimuth relationships, only a specific one or more azimuth relationships are selected. As a result, the β-phase PH2 and the α 2 -phase PH1 extend in a specified direction to form the direction control region OA.
[0180] Figure 2 , Figure 10 and Figure 32 are cross-sectional photographs including the Z direction and the Y direction of a structure obtained by a scanning method of different beams and a D1 / D0 laminated molding. Figure 2 , Figure 10 and Figure 32 each fabricated a structure of TiAl alloy (Ti-44Al-6Nb-1.2Cr). The structure is configured as a structure composed of one solidified portion.
[0181] Figure 2 In, it was adjusted so that the scanning direction of the beam when forming the j-th layer (j is a natural number) solidified layer SLj is parallel (X scan) to the scanning direction of the beam when forming the (j - 1)-th layer solidified layer SLj-1. And, the ratio (= D1 / D0) of the filling pitch D1 to the width D0 of the molten pool MP is 0.10, satisfying the formula (1). As a result, as Figure 2 shown, the fabricated structure has a direction control region OA in which the α 2 -phase PH1 and the β-phase PH2 extend in the stacking direction Z. Moreover, the cross-section including the Z direction of the entire structure (5 mm × 5 mm × 15 mm) is substantially the direction control region OA.
[0182] Figure 10 In, it was adjusted so that the scanning direction of the beam when forming the j-th layer (j is a natural number) solidified layer SLj intersects at 90° (X scan) with the scanning direction of the beam when forming the (j - 1)-th layer solidified layer SLj-1. And, the ratio (= D1 / D0) of the filling pitch D1 to the width D0 of the molten pool MP is 0.10, satisfying the formula (1). As a result, as Figure 10 shown, the fabricated structure has a direction control region OA in which the α 2 -phase PH1 and the β-phase PH2 extend at an angle of 45° with respect to the stacking direction Z. Moreover, the cross-section including the Z direction of the entire structure (5 mm × 5 mm × 15 mm) is substantially the direction control region OA.
[0183] On the other hand, Figure 32In this case, although the adjustment was made such that the scanning direction of the beam when forming the solidified layer SLj of the j-th layer (j is a natural number) was parallel to the scanning direction of the beam when forming the solidified layer SLj-1 of the (j-1)-th layer (X scanning), the ratio of the filling pitch D1 to the width D0 of the molten pool MP (= D1 / D0) was 0.37, which did not satisfy Equation (1). As a result, as Figure 32 shown, the fabricated structure did not form the α 2 phase PH1 and the β phase PH2 in the direction control region OA extending along the specified direction, and the structure (5 mm × 5 mm × 15 mm) was polycrystalline.
[0184] The above test results show that by adjusting in such a way that the scanning direction of the beam when forming the solidified layer SLj of the j-th layer (j is a natural number) is parallel to the scanning direction of the beam when forming the solidified layer SLj-1 of the (j-1)-th layer (X scanning) or in a 90° staggered manner (XY scanning), and scanning the beam in such a way that the width D0 of the molten pool MP and the filling pitch D1 satisfy Equation (1), the structure of the present embodiment can be realized.
[0185] It should be noted that the shape of the solidified layer SLk is not limited to the shape of the lower solidified layer SLk-1, and can be set to a shape larger than the solidified layer SLk-1 or a shape smaller than it. Also, one or more gaps can be formed in the shape of the solidified layer SLk. At this time, the structure can have a shape such as a closed space or a complex hole shape that cannot be obtained by conventional machining. Through the above manufacturing method, the structure of the present embodiment can be manufactured.
[0186] [Manufacturing method for forming the γ phase in the α 2 phase]
[0187] When forming the γ phase PH3 in the α 2 phase PH1 as in the structure of the second embodiment, the following heat treatment is performed on the structure manufactured by the above-described layer stacking molding method. The heat treatment temperature is set to, for example, 600 to 1300 °C. The holding time at the heat treatment temperature is not particularly limited, and is set to, for example, 1 second to 1000 minutes. By performing the above heat treatment, in accordance with the orientation relationship of Blackburn, the (0001) plane of the α 2 phase is parallel to the {111} plane of the γ phase and the <11-21> orientation of the α 2 phase is parallel to the <1-10> orientation of the γ phase, and the γ phase PH3 extending alternately with the extending direction of the α 2 phase PH1 is generated in the α 2 phase PH1. Through the above manufacturing process, the structure of the second embodiment can be manufactured.
[0188] It should be noted that Figure 6The structure is obtained by holding the structure of Figure 2 at 850 °C for 60 minutes and then air-cooling it to room temperature. Additionally, Figure 12 the structure is obtained by holding the structure of Figure 10 at 850 °C for 60 minutes and then air-cooling it to room temperature.
[0189] Furthermore, it is also possible to form the γ-phase PH3 in the α 2 phase PH1 by a method different from the method of performing heat treatment on the structure manufactured by the laminated object manufacturing method, such as the structure of the second embodiment. Specifically, after performing the melting process (S24) to form the solidified layer SLk, heat treatment based on additional beam irradiation is performed on the formed solidified layer SLk, thereby forming the γ-phase PH3 in the α 2 phase PH1 of the solidified layer SLk. When this method is adopted, heat treatment can be performed during the laminated object manufacturing process. Therefore, the structure manufactured by the laminated object manufacturing method contains the γ-phase PH3 in the α 2 phase PH1 even if heat treatment is not performed subsequently.
[0190] The embodiments of the present invention have been described above. However, the above embodiments are merely examples for implementing the present invention. Therefore, the present invention is not limited to the above embodiments, and appropriate modifications can be made to the above embodiments within the scope not departing from its gist for implementation.
[0191] Explanation of reference numerals
[0192] PH1 α 2 phase
[0193] PH2 β-phase
[0194] PH3 γ-phase
[0195] SA Solidified part
Claims
1. A structure which is a structure containing a TiAl alloy, having a solidified portion composed of a TiAl alloy, wherein the metallographic structure of the solidified portion has a cross-section including a direction control region; The α of the direction control region 2 phase and the β phase are alternately arranged, and the α 2 phase extends along a specified direction, and the β phase extends along the extension direction of the α 2 phase.
2. The structure according to claim 1, wherein, The cross section of the metallographic structure of the solidified portion further includes 2 The phase contains and is related to the α 2 The γ phase extends in a staggered direction.
3. The structure according to claim 1 or claim 2, wherein, The α in the cross-section 2 and the length of the extension direction of the β phase are 500 μm or more.
4. The structure according to claim 1 or claim 2, wherein, the structure is composed of the solidified portion of the TiAl alloy, and the cross-section is composed of the direction control region.
5. The structure according to claim 1, further having a sintered portion which is a sintered body of an inorganic material.
6. The structure according to claim 1, further having a gap formed between adjacent solidified portions.
7. A method for manufacturing a structure, comprising: a design process for determining a scanning method of a beam for forming the structure to be manufactured; and a forming process for scanning the beam based on the scanning method of the beam determined in the design process to melt inorganic powder particles which are raw materials of the structure and form the structure, in the design process, dividing the structure to be manufactured into a plurality of solidified layers in a stacking direction and determining the scanning method of the beam in each solidified layer, in the forming process, alternately repeating a layer forming process and a melting process to stack a plurality of the solidified layers and form the structure according to claim 1, wherein the layer forming process supplies the inorganic powder particles to a base to form an inorganic powder layer, and the melting process scans the beam based on the scanning method of the beam determined in the design process to melt the inorganic powder layer and form the solidified layer, the forming process is further performed as follows: adjusting so that the scanning direction of the beam when forming the j-th solidified layer is parallel to or intersects at 90° with the scanning direction of the beam when forming the (j - 1)-th solidified layer, where j is a natural number; in the scanning of the beam in each layer, scanning the beam in such a manner that the width D0 of the molten pool at a position rising by an amount equivalent to the height of the inorganic powder layer from the vertex of the molten pool having a downwardly convex shape in a cross-section perpendicular to the scanning direction of the beam and the filling pitch D1 which is the interval between adjacent scanning lines in the scanning of the beam in the same layer satisfy the formula (1), 0 < D1 / D0 ≤ 0.20 (1).
8. The method for manufacturing a structure according to claim 7, further comprising: a heat treatment process for performing heat treatment on the manufactured structure with the heat treatment temperature set to 600 to 1300 °C to manufacture the structure according to claim 2.
Citation Information
Patent Citations
MANUFACTURING METHOD OF TiAl ALLOY-MADE IMPELLER AND TiAl ALLOY-MADE IMPELLER
JP2020079577A